EU-ACP Economic Partnership Agreements - Empirical Evidence for Sub-Saharan Africa - Sebastian Vollmer; Inmaculada Martínez-Zarzoso; Felicitas Nowak-Lehmann D.; Nils Klann (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
Since early 2008 interim trade agreements between the EU and six regions of ACP countries (respectively sub-groups within the region) are in force. These agreements could be stepping stones towards full Economic Partnership Agreements between the EU and all ACP countries. We estimate the welfare effects of the interim agreements for nine African countries: Botswana, Cameroon, Côte d'Ivoire, Ghana, Kenya, Mozambique, Namibia, Tanzania, and Uganda. Our analysis is based on highly disaggregated data for trade and tariffs (HS six digit level) and follows a simple analytical model by Milner et al. (2006) to quantify the welfare effects of trade liberalization. We extend the literature in two principal ways: First, we estimate elasticities of import demand for the nine African countries importing from the EU and Sub-Saharan Africa respectively. Second, we apply the actual tariff reduction rates recently negotiated between the EU and the African countries to estimate the agreement's welfare effects of trade liberalization for the African countries. Results indicate that Botswana, Cameroon, Mozambique, and Namibia will significantly profit from the interim agreements, while the trade effects for Côte d'Ivoire, Ghana, Kenya, Tanzania, and Uganda are close to zero. However, Tanzania and Uganda also have the potential to experience positive welfare effects, but predicted results of the liberalization based on the interim agreement's reduction rates fall short of the potential of a full liberalization.
Keywords: F10; F16; O24; O11; 330; Economic Partnership Agreements; Africa; trade liberalization; tariff reduction; welfare analysis; ACP countries